The complexity of evaluating, categorising and quantifying marine cultural heritage. (February 2023) - Strand, M.; Rivers, N.; Snow, B.
Abstract: Despite the growing recognition that ecosystem-based management approaches to ocean governance need to recognise and integrate cultural dimensions to remain relevant, efficient, inclusive and equitable, the difficulty of meaningfully integrating these in ecosystem-based ocean management remains a challenge. This is particularly due to i) the difficulty of quantifying marine cultural heritage and cultural connections, ii) the complexity of identifying, evaluating and categorising 'cultural ecosystem services', particularly when it comes to intangible cultural heritage, and iii) the difficulty of spatially defining cultural heritage, connections and ecosystem services. There are several problems with current understandings and evaluations of marine cultural heritage, connections and cultural ecosystem services that first need to be addressed before attempting to quantify the social and cultural dimensions implicit in ecosystem-based ocean management. Challenges include the exclusion of some cultural 'services' that cannot be attributed an economic value because they are intangible, and the larger issue of Western-dominated conceptualisations, e.g., 'services', 'ecosystems', 'nature', 'culture'. In this short communication we argue that the quantifying and simplification of marine cultural heritage and connections should be avoided altogether, as this can result in ecosystem collapse instead of ecosystem flourishing. The piece concludes by arguing that we need to qualify instead of quantify cultural dimensions of ecosystem-based ocean management, and develop contextual participatory research methodologies to better understand marine cultural heritage and cultural connections to marine social-ecological systems.